2002
DOI: 10.1177/009579802237539
|View full text |Cite
|
Sign up to set email alerts
|

Development of Logical Reasoning and the School Performance of African American Adolescents in Relation to Socioeconomic Status, Ethnic Identity, and Self-Esteem

Abstract: This study explored the deductive reasoning and school performance of 330 African American adolescents and the relation of reasoning and school performance to socioeconomic status (SES), ethnic identity, and self-esteem. As expected, there was a systematic increase in selection task reasoning performance across adolescence, and high SES students outscored low SES students in reasoning performance and school grades. Ogbu’s cultural-ecological theory, which predicts an inverse relationship between cognitive perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 48 publications
2
33
1
Order By: Relevance
“…These above findings mirror findings with more formal tasks of deduction given to children of similar ages, such as the Wason selection task and other conditional tasks (Amsel et al, 2008;Chapell & Overton, 2002;Markovits & Thompson, 2008). For example, Markovits et al (1996) investigated conditional reasoning in 7 to 12 year-olds.…”
Section: Dual Transitive 38supporting
confidence: 66%
See 1 more Smart Citation
“…These above findings mirror findings with more formal tasks of deduction given to children of similar ages, such as the Wason selection task and other conditional tasks (Amsel et al, 2008;Chapell & Overton, 2002;Markovits & Thompson, 2008). For example, Markovits et al (1996) investigated conditional reasoning in 7 to 12 year-olds.…”
Section: Dual Transitive 38supporting
confidence: 66%
“…If and only if we use the non-training paradigm, we see a different side to transitivity, a capacity which both links to wider work on deductive reasoning in children and also to skills children acquire and improve during their schooling (Chapell & Overton, 2002;Rabinowitz & Howe, 1994;Wright, 2006b). …”
Section: Dual Transitive 38mentioning
confidence: 99%
“…Serna & A. Serna, 2015). By the time the students propose to university, they would already have much experience to deal with logic (Chapell & Overton, 2002), even though many earlier assignments at elementary and secondary level do not assign them as logic. In Indonesian educational system, students formally start learning about logics when they are at senior-high school (Depdiknas, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, Guerrier et al (2012, p. 369) pointed out that university and college faculty commonly complain that many tertiary students lack the logical competences to learn advanced mathematics, especially proofs and other mathematical activities that require deductive reasoning. This means that although the students have experienced to deal with logical problems; however, it does not guarantee that they understand the essence of logics (Chapell & Overton, 2002;OECD, 2016, p. 5) and logics is still doubtly difficult to study amongst learners (Guha, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In their study of 85 male and female African American 1 lth-and 12'~-grade high school students, the authors found that ethnic identity achievement was related to greater career decisionmaking self-efficacy. This finding is not surprising given the literature on ethnic identity and its importance in the development of self-esteem and psychological adjustment in ethnic minority adolescents and young adults (Chapell & Overton, 2002;Phinney & Alipuria, 1990;Smith & Brookins, 1997).…”
Section: Career Decision Self-efficacy (Cdse)mentioning
confidence: 73%